2013
DOI: 10.1007/s10753-013-9732-x
|View full text |Cite
|
Sign up to set email alerts
|

Thymol Inhibits LPS-Stimulated Inflammatory Response via Down-Regulation of NF-κB and MAPK Signaling Pathways in Mouse Mammary Epithelial Cells

Abstract: Thymol is a natural monoterpene phenol primarily found in thyme, oregano, and tangerine peel. It has been shown to possess anti-inflammatory property both in vivo and in vitro. In the present paper, we studied the anti-inflammatory effect of thymol in lipopolysaccharide (LPS)-stimulated mouse mammary epithelial cells (mMECs). The mMECs were stimulated with LPS in the presence or absence of thymol (10, 20, 40 μg/mL). The concentrations of tumor necrosis factor α (TNF-α), interleukin (IL)-6, and IL-1β in the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
106
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 37 publications
9
106
0
Order By: Relevance
“…Both thymol and carvacrol significantly decreased STAT-3 and SAPK/JNK phosphorylation in the stimulated macrophage cells (total cell extract); this suggested to us the probable ability of these agents to diminish STAT-3-and JNKmediated activity of cytokines associated with inflammatory responses (Kortylewski et al, 2009). It should be mentioned that, in a previous study on total cell extract of LPS-stimulated mouse mammary epithelial cells, thymol decreased the levels of phosphorylation of NF-jB p65, IjBa, JNK, ERK and p38 MAPK after 1 h (Liang et al, 2014). In the current study, according to results of the ELISA assays, carvacrol and thymol also inhibited phosphorylation of IjBa, JNK and STAT-3.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Both thymol and carvacrol significantly decreased STAT-3 and SAPK/JNK phosphorylation in the stimulated macrophage cells (total cell extract); this suggested to us the probable ability of these agents to diminish STAT-3-and JNKmediated activity of cytokines associated with inflammatory responses (Kortylewski et al, 2009). It should be mentioned that, in a previous study on total cell extract of LPS-stimulated mouse mammary epithelial cells, thymol decreased the levels of phosphorylation of NF-jB p65, IjBa, JNK, ERK and p38 MAPK after 1 h (Liang et al, 2014). In the current study, according to results of the ELISA assays, carvacrol and thymol also inhibited phosphorylation of IjBa, JNK and STAT-3.…”
Section: Discussionmentioning
confidence: 83%
“…NF-jB is one of the most ubiquitous important transcription factors that regulate gene expression, including that of iNOS, COX-2, cytokines TNFa and IL-1b, as well as chemokines and adhesion molecules involved in regulation of inflammatory responses (Chen et al, 1999;Liang et al, 2014). We hypothesized that thymol and carvacrol could inactivate this transcription factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Z. tenuior [94] Anti-genotoxic (bleomycin-induced DNA damage) [287] Z. tenuior [94] Anti-genotoxic (bleomycin-induced DNA damage) [287] Anti-inflammatory activity in carrageenan-induced paw edema, MPO activity and peritonitis in rats [288]; anti-inflammatory activity in LPS-stimulated mouse mammary epithelial cells via inhibition of the NF-κB and MAPKs signalling pathways [289]; antiinflammatory effect in ovoalbumin-induced mouse asthma, possibly through inhibiting NF-κB activation [290]; inhibition of S. aureus internalization into bovine mammary epithelial cells by inhibiting NF-κB activation [291] Review on anti-inflammatory, antioxidant, and immunological effects [292] Protective effect on radiation-induced apoptosis in Chinese hamster lung fibroblast V79 cells [293]; DNA-protective effects against H2O2-induced DNA lesions in human hepatoma HepG2 cells [294]; hepatoprotective effect against t-BHP-induced oxidative damage in Chang liver cells [84]; protective effect against cisplatin-induced nephrotoxicity in rats [295]; protective effect against UVA-and UVB-induced lipid peroxidation in NCTC 2544 cell line Z. clinopodioides subsp. rigida (8%) [21] Z. tenuior [94] Anti-genotoxic (bleomycin-induced DNA damage) [287] Anti-inflammatory activity in carrageenan-induced paw edema, MPO activity and peritonitis in rats [288]; anti-inflammatory activity in LPS-stimulated mouse mammary epithelial cells via inhibition of the NF-κB and MAPKs signalling pathways [289]; anti-inflammatory effect in ovoalbumin-induced mouse asthma, possibly through inhibiting NF-κB activation [290]; inhibition of S. aureus internalization into bovine mammary epithelial cells by inhibiting NF-κB activation [291] Review on anti-inflammatory, antioxidant, and immunological effects [292] Protective effect on radiation-induced apoptosis in Chinese hamster lung fibroblast V79 cells [293]; DNA-protective effects against H 2 O 2 -induced DNA lesions in human hepatoma HepG2 cells [294]; hepatoprotective effect against t-BHP-induced oxidative damage in Chang liver cells [84]; protective effect against cisplatin-induced nephrotoxicity in rats [295]; protective effect against UVA-and UVB-induced lipid peroxidation in NCTC 2544 cell line...…”
Section: Ohmentioning
confidence: 99%
“…It was shown that thymol could decrease phosphorylation of several signaling molecules such as NF-κB p65, IκBα, c-Jun NH(2)-terminal protein kinases (JNK), extracellular signal-regulated kinases (ERK) and p38 mitogenactivated protein kinases (MAPK) in these cells. 21 Considering the central role of T cells in inflammatory processes, in the present study we aimed to investigate the effects of these components on T cells in order to derive a better understanding of the mechanisms underlying their anti-inflammatory effects. In addition, as altered T cell function is often a key component associated with numerous pathologies, discerning how they may affect T cells can help scientists build upon our findings and take better advantage of these natural products.…”
Section: Introductionmentioning
confidence: 99%